Race of GLPS: Impact on Weight and Glycemic Control on Type 2 Diabetes with Semaglutide Versus Liraglutide - Noha Hafeez; Fatima Jehanghir; Aroosa Altaf; Huma Akbar Jafri; Tariq Adnan; Faiza Rani Ahmed; Naureen Kazim (Journal of Gandhara Medical and Dental Sciences)
OBJECTIVES